Pengaruh Kematangan Pribadi Dengan Kecenderungan Cinderella Complex Pada Wanita Dewasa Awal - Zahrawaany, Tasya Aulia; Fasikhah, Siti Suminarti (Faculty of Psychology, University of Muhammadiyah Malang, Indonesia, 2019)
A healthy person is a person who always develops in new states that require adjustment, while an unhealthy individual is when individuals do not use the potential that can be maintained and used in their lives, specifically for women who actually can increase their potential. The purpose of this study was to study the infuency of personal maturity towards Cinderella Complex in early adult women. This study used a correlational research design, using a accidental sampling technique with help of google form. The subjects were 2956 early adult women aged 18-25 years. The instrument in this study used a scale of personal maturity and the scale of the findings of the cinderella complex inventory. Data analysis using simple linear regression analysis. The results showed that there were effect of personal maturity towards complex cinderella tendencies in early adult women. The value of regression coefficient is -0.390 with p = 0,000 <0.05. This result shows that the higher the personal maturit in earl adult woman, the lower cinderella complex tendency in individuals. The influence of personal maturity towards the tendency of Cinderella complex in early adult women is about 34.7%. This research can be used as a material consideration to arrange psychoeducation program as a preventive effort.